PENGARUH CITRA MEREK, KUALITAS PRODUK, DAN MEDIA SOSIAL DALAM KEPUTUSAN PEMBELIAN PADA PUAN KOPI BALIKPAPAN - Ferina, Nabila; Indriastuty, Nina; Hernadi Moorcy , Nadi (MEDIA RISET EKONOMI [MR.EKO], 2025)
The purpose of this research is to determine the partial effects of brand image, product quality, and social media on purchase decisions at Puan Coffee Balikpapan. The population for this study consists of 600 individuals, with a sample size of 187 taken in June 2024 using probability sampling techniques based on predetermined criteria. The method employed is multiple linear regression. The results show that social media, brand image, and product quality significantly influence the variables and purchase decision intentions at Puan Coffee Balikpapan. The partial test results indicate that brand image and product quality have a positive and significant effect on purchase decisions, while social media does not have a significant impact on purchase decisions at Puan Coffee Balikpapan.